EFEKTIFITAS PEMBERIAN FAMILY PSYCHOEDUCATION (FPE) TERHADAP KEPATUHAN MINUM OBAT PENDERITA SKIZOFRENIA DI KOTA KEDIRI - Dhita Kurnia Sari; Lingga Kusuma Wardani (STRADA : Jurnal Ilmiah Kesehatan, 2017)
ABSTRACT THE EFFECTIVENESS OF FAMILY PSYCHOEDUCATION (FPE) ON DRUG SUBSTITUTION OF SKIZOFRENIA PATIENTS IN THE CITY OF KEDIRI Dhita Kurnia Sari 1, Lingga Kusuma Wardani 2 STIKes Surya Mitra Husada Kediri deeniasari88@gmail.com Schizophrenia is one type of psychotic disorders that often experience relapse. About 33% of people with schizophrenia experience recurrence and about 12.1% re-experienced hospitalization. Discontinuation of drugs is a major cause of recurrence of schizophrenic patients. The family of schizophrenic patients is a very important variable in the recurrence of schizophrenic patients. Allegedly the biggest factor in its effect on adherence to taking the drug of schizophrenia is family factor. The purpose of this study is to determine the effectiveness of family psychoeducation therapy on adherence to taking the drug of schizophrenia patients. The design used in this research is pre-experiment. The population in the study were all families of schizophrenic patients in Kediri. Sampling technique in this research is taken by Purposive Sampling. The independent variable is the provision of family psychoeducatin therapy and the dependent variable in this study is the adherence to taking the drug of schizophrenic patients. Data were collected by observation sheet, then analyzed using Mc Nemar test with significance level aÂ£ 0,05. The results of the study of adherence to the treatment of schizophrenic patients before given the family psychoeducation of 20 respondents who did not obey 20 respondents (100%), whereas after given the family psychoeducation obedient 17 (85%) and disobedient 3 (15%), from the results of statistical tests with using Mc Nemar test obtained p value 0,000 <Î± 0.05 means there is influence of adherence to medication before and after given family psycoeducation. Family knowledge and ability to cope with stressors while caring for family members with schizophrenia can create a comfortable and conducive environment that helps restore the client's condition and reduce and prevent noncompliance with schizophrenia medication. Keywords: adherence, family psychoeducation, schizophrenia